THE LEARNING OF SCIENCES: A GRADUAL CHANGE IN THE WAY OF LEARNING. THE CASE OF VISION - Bravo, Bettina M.; Pesa, Marta A.; Pozo, Juan Ignacio (Investigações em Ensino de Ciências, 2016)
Learning the scientific way of knowledge implies a change in the most implicit principles that guide comprehension, interpretation and explanation of scientific phenomena as well as a change in the type of associated reasoning. With the aim of favouring this type of learning, a teaching programme was developed in relation to vision and implemented with a group of secondary school students. The way of learning of these students was observed at different teaching stages. Findings suggest that during the learning process the way students learn seems to change gradually and that students construct “intermediate” models (right but incomplete) that become the basis for the construction of a systemic model proposed by school science.